NUTRARET: Effect of 2-Year Nutraceutical Supplementation on Redox Status and Visual Function of Patients With Retinitis Pigmentosa: A Randomized, Double-Blind, Placebo-Controlled Trial - Olivares-González, Lorena; Salom, David; González-García, Emilio; Hervás, David; Mejía-Chiqui, Natalia; Melero, Mar; Velasco, Sheyla; Muresan, Bianca Tabita; Campillo, Isabel; Vila-Clérigues, Nieves; López-Briz, Eduardo; Merino-Torres, Juan Francisco; et al. (Frontiers in Nutrition, 2022)
Oxidative stress plays a major role in the pathogenesis of retinitis pigmentosa (RP). The main goal of this study was to evaluate the effect of two-year nutritional intervention with antioxidant nutraceuticals on the visual function of RP patients. Secondly, we assessed how nutritional intervention affected ocular and systemic redox status. We carried out a randomized, double-blind, placebo-controlled study. Thirty-one patients with RP participated in the study. RP patients randomly received either a mixture of nutraceuticals (NUT) containing folic acid, vitamin B6, vitamin A, zinc, copper, selenium, lutein, and zeaxanthin or placebo daily for two years. At baseline and after two-year of the nutritional supplementation, visual function, dietetic-nutritional evaluations, serum concentration of nutraceuticals, plasma and aqueous humour concentration of several markers of redox status and inflammation were assessed. Retinal function and structure were assessed by multifocal electroretinogram (mfERG), spectral domain-optical coherence tomography (SD-OCT) and automated visual field (VF) tests. Nutritional status was estimated with validated questionnaires. Total antioxidant capacity, extracellular superoxide dismutase (SOD3), catalase (CAT) and glutathione peroxidase (GPx) activities, protein carbonyl adducts (CAR) content, thiobarbituric acid reactive substances (TBARS) formation (as indicator of lipid peroxidation), metabolites of the nitric oxide and cytokine (IL6 and TNFα) concentrations were assessed by biochemical and immunological techniques in aqueous humour or/and blood. Bayesian approach was performed to determine the probability of an effect. Region of practical equivalence (ROPE) was used. At baseline, Bayesian analysis revealed a high probability of an altered ocular redox status and to a lesser extent systemic redox status in RP patients compared to controls. Twenty-five patients (10 in the treated arm and 15 in the placebo arm) completed the nutritional intervention. After two years of supplementation, patients who received NUT presented better retinal responses (mfERG responses) compared to patients who received placebo. Besides, patients who received NUT showed better ocular antioxidant response (SOD3 activity) and lower oxidative damage (CAR) than those who received placebo. This study suggested that long-term NUT supplementation could slow down visual impairment and ameliorate ocular oxidative stress.